2016
DOI: 10.18632/oncotarget.8551
|View full text |Cite
|
Sign up to set email alerts
|

Differential localization of glioblastoma subtype: implications on glioblastoma pathogenesis

Abstract: IntroductionThe subventricular zone (SVZ) has been implicated in the pathogenesis of glioblastoma. Whether molecular subtypes of glioblastoma arise from unique niches of the brain relative to the SVZ remains largely unknown. Here, we tested whether these subtypes of glioblastoma occupy distinct regions of the cerebrum and examined glioblastoma localization in relation to the SVZ.MethodsPre-operative MR images from 217 glioblastoma patients from The Cancer Imaging Archive were segmented automatically into contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 33 publications
1
19
0
Order By: Relevance
“…U87MG (ATCC line), LN229, U251, and A172 cells were cultured in Dulbecco’s modified Eagle medium (DMEM) containing 10% fetal bovine serum (FBS). GBM patient-derived neurospheres and GSC were isolated and cultured as previously described as previously described 56 59 . For primary glia isolation, the cerebral cortex from new born mice (2 or 3 days-old) was collected, homogenized and harvested with Leibovitz’s L-15 medium.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…U87MG (ATCC line), LN229, U251, and A172 cells were cultured in Dulbecco’s modified Eagle medium (DMEM) containing 10% fetal bovine serum (FBS). GBM patient-derived neurospheres and GSC were isolated and cultured as previously described as previously described 56 59 . For primary glia isolation, the cerebral cortex from new born mice (2 or 3 days-old) was collected, homogenized and harvested with Leibovitz’s L-15 medium.…”
Section: Methodsmentioning
confidence: 99%
“…Gfap-CreER;Pten fl/fl ;Rb1 fl/fl ;Trp53 fl/fl ;Rbl1 −/− mice were obtained and induced for gliomagenesis as in 59 . The brain was analyzed at 8–12 weeks after injection.…”
Section: Methodsmentioning
confidence: 99%
“…Tumor location may correlate with distinct subtypes, clinical outcomes, and growth patterns. [14][15][16] In particular, proneural or neural GBM subtypes, based on The Cancer Genome Atlas (TCGA) system, are proximal and mesenchymal or classical TCGA subtypes are distal to the SVZ, suggesting differential cells of origin. 16 The frontal lobe is a preferential location for LGGs with IDH mutations.…”
Section: Preferential Brain Locationsmentioning
confidence: 99%
“…[14][15][16] In particular, proneural or neural GBM subtypes, based on The Cancer Genome Atlas (TCGA) system, are proximal and mesenchymal or classical TCGA subtypes are distal to the SVZ, suggesting differential cells of origin. 16 The frontal lobe is a preferential location for LGGs with IDH mutations. 6,[17][18][19][20] Furthermore, LGGs in the frontal lobe have higher TERT promoter mutation rates compared with midline tumors that are predominantly IDH wild-type and harbor fewer TERT promoter mutations.…”
Section: Preferential Brain Locationsmentioning
confidence: 99%
“…Olig2+ cells were found in proneural glioblastomas (Verhaak et al, 2010) and studies on animal models of gliomagenesis suggested Olig2+ cells in the SVZ as a potential origin of gliomas (Wang et al, 2009), including the proneural subtype (Lu et al, 2016). Interestingly, proneural and neural glioblastomas were closer to the SVZ than the other subtypes (Steed et al, 2016). Subependymomas may arise from multipotent cells in the SVZ and express glial and stem cell markers such as GFAP, Olig2 and Sox2 (D'Amico et al, 2017).…”
Section: Brain Cancers Arising From the Svz: Clinical Gliomas And Epementioning
confidence: 99%